FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA - Hasriyono, Kurnia Mulindawati; Diandra, Prita Karina (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to obtain empirical evidence whether current ratio, return on assets, net profit margin, and company size affect earnings growth. This research method uses quantitative analysis. The population in this study are all companies in the consumer non-cyclicals, technology and health sectors listed on the Indonesia Stock Exchange (IDX) consecutively from 2021-2023. This study uses a nonprobability sampling method with purposive sampling technique with a 3-year period. So that in this study there were 69 company samples. The results showed that current ratio, net profit margin and company size have no effect on earnings growth. While return on assets affects profit growth. However, simultaneously current ratio, return on assets, net profit margin and company size affect profit growth.